2018
DOI: 10.1097/bpb.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Guided growth for caput valgum in developmental dysplasia of the hip

Abstract: Therapeutic study, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…There are several case series about eccentrical transphyseal screws for coxa valga in patients with developmental dysplasia of the hip and/or cerebral palsy. 44 46 To our knowledge there are no reports of the use of TBPs in these patients. Recently d’Heurle et al 47 compared screws, TBPs and drilling techniques for coxa valga in an experimental model with lambs.…”
Section: Correction Of Angular Deformitiesmentioning
confidence: 96%
“…There are several case series about eccentrical transphyseal screws for coxa valga in patients with developmental dysplasia of the hip and/or cerebral palsy. 44 46 To our knowledge there are no reports of the use of TBPs in these patients. Recently d’Heurle et al 47 compared screws, TBPs and drilling techniques for coxa valga in an experimental model with lambs.…”
Section: Correction Of Angular Deformitiesmentioning
confidence: 96%
“…Previous reports have shown satisfactory radiological results using screw hemi-epiphysiodesis for valgus deformities of the proximal femur secondary to AVN in DDH patients. [11][12][13][14][15] However, there is little in the literature comparing these two surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Later, other studies have shown improved radiological outcomes using the guided growth method. [11][12][13][14] This study is the first to compare guided growth with corrective osteotomy for this particular hip condition. The literature on the management of valgus deformity due to AVN comprises patients already treated by different procedures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations